ТЕОРІЯ ЙМОВІРНОСТЕЙ - Кушнірчук, Василь Йосипович (Видавництво Чернівецького національного університету імені Юрія Федьковича, 2024)
The textbook outlines the basic concepts of the course "Probability Theory", which the author teaches to students of the Faculty of Mathematics and Informatics and the Faculty of Economics. In addition to the theoretical material, the textbook contains practical problems for each chapter. The textbook will be useful for students and anyone who wants to get acquainted with the basic concepts of probability theory.
PROBABILITY THEORY
Keywords: теорія ймовірностей; випадкова подія; ймовірність події; випадкова величина; математичне сподівання; дисперсія; probability theory; random event; event probability; random variable; mathematical expectation; variance